Remote aerospace research as an interdisciplinary scientific trend in nature management - Fedorovsky, A.D.; Sokolovska А.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The paper proves the interdisciplinary scientific directivity of the remote sensing by the example of evaluating the oil- and gas-bearing areas of the Caspian shelf in Turkmenistan. The relevant informative signs of the presence of hydrocarbon deposits (including reference areas) are defined, and their values across the shelf waters are calculated involving knowledge from different scientific disciplines such as geology, hydrology, hydrophysics, and iconics. In the final stage of the research, the evaluation of the oil- and gas-bearing areas is done, by basing on the hierarchies analysis method with a generalized criterion.